The Effect of Time Budget Pressure, Audit Fee, and Auditor Independence on Audit Quality - Subiyanto, Bambang; Pradani, Tiara; Asiyah, Nur (International Journal of Accounting & Finance in Asia Pasific (IJAFAP), 2023)
This study aims to determine the effect of time budget pressure, audit fees, and auditor independence on audit quality. Quantitative data is used in this study. The data used in this study is primary data. The data was obtained by distributing questionnaires to the respondents, and the data was processed in as many as 92 questionnaires. The population in this study are auditors who work at a foreign-affiliated Public Accounting Firm (KAP) in Jakarta. The test was carried out with the help of IBM SPSS statistic 25. The results showed that time budget pressure affects audit quality. Audit fees also do not affect audit quality. Lastly, auditor independence affects audit quality. Further research can add other variables and expand the scope of respondents.